2020
DOI: 10.1038/s41598-020-69762-w
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation effects on the clinical outcomes of patients with coronary artery disease: a systematic review and meta-analysis

Abstract: In this systematic review and meta-analysis our aim was to assess the effect of vitamin D supplementation on cardiac outcomes in patients with coronary artery disease (CAD). The search terms were performed from January 2000 to January 2018, only randomized clinical trials (RCT) in human subjects were considered, with no language restrictions. The electronic databases used in this study were: PubMed; Cochran library; Embase; and Scopus. Two independent expert reviewers carried out data extraction according to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Evidence from previous studies revealed that 25OHD deficiency resulted in the increase expression of inflammatory factors, such as interleukin 6, interleukin 8, and C-reactive protein [ 37 ], which play important roles in CAD. Furthermore, low serum 25OHD levels are associated with obesity, dyslipidemia, the metabolic syndrome, and hypertension, which are all well-established CAD risk factors [ 9 , 10 ]. It was shown that lower serum bioavailable and free 25OHD levels were associated with prevalent cardiovascular mortality independent of other recognized cardiovascular risk factors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from previous studies revealed that 25OHD deficiency resulted in the increase expression of inflammatory factors, such as interleukin 6, interleukin 8, and C-reactive protein [ 37 ], which play important roles in CAD. Furthermore, low serum 25OHD levels are associated with obesity, dyslipidemia, the metabolic syndrome, and hypertension, which are all well-established CAD risk factors [ 9 , 10 ]. It was shown that lower serum bioavailable and free 25OHD levels were associated with prevalent cardiovascular mortality independent of other recognized cardiovascular risk factors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, serum 25-hydroxyvitamin D (25OHD) is an important indicator of vitamin D status [ 8 ]. Lots of evidence has been accumulated that low level of serum 25OHD levels were associated with cardiovascular risk factors, such as obesity, dyslipidemia and hypertension [ 9 , 10 ]. In addition, previous study showed that 25OHD may affect endocrine and cardiovascular systems via its nuclear receptor (25-hydroxyvitamin D receptor (VDR)) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low serum 25OHD levels are associated with obesity, dyslipidemia, the metabolic syndrome, and hypertension, which are all well-established CAD risk factors. [33,34] It was shown that lower serum bioavailable and free 25OHD levels were associated with prevalent cardiovascular mortality independent of other recognized cardiovascular risk factors. [35] Vitamin D de ciency might be considered a so-called "nonclassical" CAD risk factor in studies without a speci c focus on diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis Martineau et al 153 Nursyam et al 175 Morcos et al 176 Wejse et al 177 Influenza Aloia and Li-Ng, 43 AIDS Arpadi et al 178 Reviewed in Alvarez et al, 2019 and Teixeira et al 29,31 Schistosomiasis Snyman et al 179 Sepsis Amrein et al 180 Leaf et al 181 Quraishi et al 182 Miroliaee et al 183,184 Ginde et al 151 Coronary disease Sokol et al 185 Farrokhian et al 186 Bahrami et al 187,188 Manson et al 28 Diabetes Pittas et al 30 Multiple sclerosis Kouchaki et al 34 Berezowska et al 35 Dengue Ahmed et al 32 Martinez-Moreno et al 33 Selected clinical studies of vitamin D supplementation and meta-analysis of multiple disease-relevant clinical trials showing infection or disease protective effects are presented.…”
Section: Disease Referencesmentioning
confidence: 99%